Treasure Island. - Stevenson, Robert Louis (Oxford Bookworms, 2008)
Suddenly, there was a high voice screaming in the darkness: "Pieces of eight! Pieces of eight! Pieces of eight!" It was Long John Silver's parrot, Captain Flint! I turned to run... ' But young Jim Hawkins does not escape from the pirates this time. Will he and his friends find the treasure before the pirates do? Will they escape from the island, and sail back to England with a ship full of gold?